2009
DOI: 10.1177/1077801208331063
|View full text |Cite
|
Sign up to set email alerts
|

Collecting Reliable Information About Violence Against Women Safely in Household Interviews

Abstract: This article describes the first national survey of violence against women in Pakistan from 2001 to 2004 covering 23,430 women. The survey took account of methodological and ethical recommendations, ensuring privacy of interviews through one person interviewing the mother-in-law while another interviewed the eligible woman privately. The training module for interviewers focused on empathy with respondents, notably increasing disclosure rates. Only 3% of women declined to participate, and 1% were not permitted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 24 publications
0
32
0
1
Order By: Relevance
“…As reporting rates might vary in relation to risk factors, it can be a source of bias. A major determinant of GBV reporting in surveys is the quality of training of the fieldworkers [142]. A study in Lesotho showed that other contexts were also important: women living in GBV awareness project areas, presumably reflecting increased awareness, were more likely to report a history of sexual violence [143].…”
Section: Observational Studiesmentioning
confidence: 99%
“…As reporting rates might vary in relation to risk factors, it can be a source of bias. A major determinant of GBV reporting in surveys is the quality of training of the fieldworkers [142]. A study in Lesotho showed that other contexts were also important: women living in GBV awareness project areas, presumably reflecting increased awareness, were more likely to report a history of sexual violence [143].…”
Section: Observational Studiesmentioning
confidence: 99%
“…Estos autores explican que, a medida que una sociedad se desarrolla económicamente y las mujeres adquieren los derechos políticos y sociales, y acceden al trabajo y la educación, existe una mayor posibilidad de escapar de la situación de violencia. Existe una relación entre la pobreza y la violencia familiar, así como entre el nivel educativo y socio-económico bajo y la violencia conyugal (Andersson, Cockcroft., Ansari, Omer, Chaudhry, Khan y Pearson, 2009;Echeburúa, Amor y De Corral, 2002;Tokuç et al, 2010). Otros estudios han encontrado que en los paí-ses en vías de desarrollo, los niveles de violencia contra mujeres embarazadas son mayores que en las sociedades más desarrolladas (Campbell, García-Moreno y Sharps, 2004;Kaya y Cook, 2010;Nasir y Hyder, 2003;Tokuç et al, 2010).…”
Section: Factores De Riesgo Asociados Al Macrosistemaunclassified
“…The Aurat Foundation (2012) also reports that relatives such as husband, brother, cousin, father, uncle, father and mother-in-law, brother-in-law, son or step son remain the most common perpetrators of VAW. Though such evidence is important and provides an insight in to the extent of VAW in Pakistan, empirical evidence about IPV in Pakistan is scarce (Andersson, Cockcroft, Ansari, Omer, Chaudhry et al, 2009). No attempt has so far been made to aggregate and systematically review the evidence related to IPV in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…For example, various Non-Governmental Organizations (NGOs) such as the Human Rights Commission for Pakistan provide some evidence of VAW, typically obtained from the press and official bodies such as the police (Andersson, Cockcroft, Ansari, Omer, Chaudhry et al, 2009). According to the figures provided by Aurat Foundation (2013), during 2012 a total of 7516 cases of VAW across the country were reported.…”
Section: Introductionmentioning
confidence: 99%